On R&D sectoral intensities and convergence clubs - Sebastiano Cattaruzzo (European Commission, Joint Research Centre (JRC), 2020)
Sectoral convergence in R&D intensities among firms is a concept that, although rarely formalized, has been at the center of discussions of industrial and non-industrial actors, such as entrepreneurs, institutions and academics. Far from being a settled issue, the subject has seen very limited empirical attention. We start from the few current evidences, which point to the existence of some beta-convergence together with diffused heterogeneity. We recover and integrate the literature from convergence clubs and extend the work introducing the use of Pavitt taxonomy, and new estimation techniques. Particularly, we apply the concept of weak sigma-convergence using a quite novel econometric factor model. Thanks to this, we provide evidences of both beta-convergence for within-sector intensities and of club convergence for across-sector intensities. Finally, the club classification according to "innovative effort" may be used as an alternative way to look at standard economic activities classifications.
Keywords: 330; Industrieforschung; Branche; Faktorintensität; Wirtschaftliche Konvergenz; Welt